E-Animation Media to Improve The Understanding of Elementary School Science Learning - Zakirman Zakirman; Chichi Rahayu; Wienda Gusta (Jurnal Basicedu, 2022)
This research was motivated by the low mastery of student learning in science learning, especially in light-matter because of the lack of use of learning media that is in accordance with the characteristics of the material in Class V elementary school. The purpose of this study was to analyze the effect of using Macromedia flash-based electronic learning media on the material properties of light in improving the learning outcomes of fifth-grade elementary school students. Learning outcomes used as research data are limited to the cognitive domain. The material selected in the research was the properties of light. This type of research was quasi-experimental, where the samples taken in research activities were fifth-grade students at SDN 12 Nan Sabaris. The instrument used was a multiple-choice test. The data analysis technique used a t-test. Based on the results of data analysis obtained t-count with a value of 6.91 and t-table with a value of 2.04. This means that there is a significant difference between student learning outcomes before using animation media and student learning outcomes after using animation media. Thus, it can be concluded that the use of e-animation has an effect on student learning outcomes. The use of e-animation can be a new alternative as a solution to improve the quality of learning and student understanding.